2008
DOI: 10.1002/ijc.23364
|View full text |Cite
|
Sign up to set email alerts
|

Site‐specific analysis of N‐glycans on haptoglobin in sera of patients with pancreatic cancer: A novel approach for the development of tumor markers

Abstract: It was found in our previous studies that the concentration of fucosylated haptoglobin had increased in the sera of patients with pancreatic cancer (PC) compared to those of other types of cancer and normal controls. Haptoglobin, an acute phase protein, has four potential N-glycosylation sites, although it remains unknown which site is responsible for the change in fucosylated N-glycans. In the present study, site-specific N-glycan structures of haptoglobin in sera obtained from patients with PC or chronic pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
158
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(164 citation statements)
references
References 29 publications
(38 reference statements)
6
158
0
Order By: Relevance
“…Nonetheless, the colorectal epithelium expression of Hp has also been previously reported (42,43). The Hp molecule is composed of two α and two β subunits, of which only β subunits are glycosylated (44). These reasons led to the selection of Hp as a putative CDw75-bearing protein.…”
Section: Discussionmentioning
confidence: 96%
“…Nonetheless, the colorectal epithelium expression of Hp has also been previously reported (42,43). The Hp molecule is composed of two α and two β subunits, of which only β subunits are glycosylated (44). These reasons led to the selection of Hp as a putative CDw75-bearing protein.…”
Section: Discussionmentioning
confidence: 96%
“…Once tryptic peptide masses are known, it becomes a simple computational exercise to match accurate glycopeptide masses (obtained via high resolution mass spectrometry) to potential peptide/glycan combinations. Tryptic digests have been used by many labs to determine the site-specific glycosylation of selected N-and O-glycosylated proteins, including ribonuclease B (a simple, well-characterized glycoprotein with one N-glycosylation site) (59); prostatic acid phosphatase (an indicator of prostate cancer) (60); bovine fetuin (a well-characterized glycoprotein with both N-and O-glycosylation) (59,61); erythropoietin (an important biotherapeutic drug) (52, 61); horseradish peroxidase (used widely in biochemistry labs as a catalyst for oxidation) (59, 62); and haptoglobin (one of the most abundant proteins in human serum) (51,59,63). However, in many cases, there are distinct disadvantages to tryptic digestion of glycoproteins.…”
Section: Glycoproteomic Approaches Towards Determining Site-specific mentioning
confidence: 99%
“…Zhao et al analyzed the site-specific glycosylation of α1-antitrypsin, an abundant serum glycoprotein, and were able to identify specific glycosylation patterns which varied with incidence of pancreatic cancer (43). Nakano et al also studied site-specific glycosylation differences in pancreatic cancer but chose instead to focus on haptoglobin, another abundant serum protein, finding specific glycoforms which differentiated pancreatic cancer patients from both chronic pancreatitis patients and normal controls (63). Thaysen-Andersen et al performed similar studies with tissue inhibitor of metalloproteinase-1 (TIMP-1), a known biomarker of colorectal cancer, and characterized several glycoforms of TIMP-1 that were unique to colon cancer cell lines (88).…”
Section: Biomarker Applications Of Glycoproteomicsmentioning
confidence: 99%
“…However, the fucosylation site of haptoglobin in prostate cancer may be different from that in pancreatic cancer, since extensive mass spectrometry of released N-linked glycans from prostate cancer cases indicated that the fucosylation site was at the peripheral GlcNAc through ·3 or ·4 fucosylation at Asn 207 and 211, rather than ·6 fucosylation at the core GlcNAc (16). Similarly, site-specific expression of sialyl-Le x in the tri-antennary N-linked glycan at the Asn 211 site of haptoglobin in pancreatic cancer was clearly demonstrated recently (18).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the N-glycosylation status of haptoglobin from sera of patients with cancer has been studied in detail (16)(17)(18). The N-glycosylation sites of haptoglobin were found exclusively in the ß-subunit and the level of N-glycosylation was enhanced at Asn 207 and 211 as compared to Asn 241 or Asn 184 of the ß-subunit isolated from prostate cancer, as compared to benign prostate disease (16).…”
Section: Introductionmentioning
confidence: 99%